Efektivitas Nutrisi AB MIX Dan Pupuk Organik Cair Terhadap Tanaman Selada (Lactuca Sativa L.) Secara Hidroponik Wick System - Khairi, Miftakhul; Sutoko, N. Adi; Al Ifah, Arini (JURNAL ILMIAH AGRINECA, 2025)
This research aims to determine the nutritional concentration of AB Mix and Liquid Organic Fertilizer which is better for the growth and yield of lettuce plants hydroponically using a wick system. This research used a Completely Randomized Design (CRD) method with a single factor of six treatment levels with three replications. The treatment factor is the provision of the amount of AB Mix nutrients and the amount of Liquid Organic Fertilizer nutrients which consist of 6 treatment levels including AB Mix N1 600 ppm, AB Mix N2 700 ppm, AB Mix N3 800 ppm, POC N4 700 ppm, POC N5 800 ppm, and POC N6 900 ppm. The data obtained was analyzed statistically using variance analysis. If the results of the variance analysis were significantly different, then further tests were carried out using Duncan's Multiple Range Test (DMRT), at the 5% level. The research showed that the AB Mix nutrient treatment with N2 with a concentration of 700 ppm provided the best growth and results compared to other therapies for lettuce plants cultivated hydroponically using a wick system.